Symbolic Study of Color in Bakhtiyari Textiles with Emphasis on Veris (Card Weaving) - Arjmandi, Nasrin; Rahmani, Ashkan; Bassam, Seyed Jalal Eddin (Journal of History Culture and Art Research, 2018)
Veris is a narrow weaving with a width of 2-10 cm. and a length of 1-8 m., often woven with woolen yarns by simple tools known as cards. This woven has a variety of applications, in the past for decorating clothes, the collar, the edge of the skirt, the belt, baby wrapping, hat bands, saddles and many other uses, the handmade strips were used. But today, more is used to decorate clothes. For the Veris weaving, the Bakhtiyari tribes use many motifs and designs most of which are based on their customs, habits, perceptions, insights, environment and their culture. In this textile, geometric, human, animal, herbal, inscription, positive and negative motifs are used. Red, black, blue, yellow, and dark green are main color in Bakhtiyari hand woven. Each of the colors in the Bakhtiyari tribes symbolizes an event. For example: red Veris for happy event, green Veris is for fastening infant and black tent, yellow Veris for expensive objects, blue Veris for fastening ordinary objects, black and white Veris for mourning events. In short, the composition of colors in the Veris depends on the type of application. This research, by examining the current literature and applying a fieldwork, implements a descriptive & analytical methodology to analyze and understand the “symbolism” in card weaving. The study will examine different motif shapes and explain the meaning of the motif among the Bakhtiyari tribes. For this purpose, different car woven samples will be illustrated and pictured for the reader. The study concludes that card weaving has decorative and functional meanings.